The Effectiveness of Identifying Learning of the Information in Explanatory Texts By Using the SQ3R Method Based on the Reading Intensity of the XI Grade Students at Madrasah Aliyah - Zulaikhah, Zulaikhah; Subyantoro, Subyantoro; Haryadi, Haryadi (Universitas Negeri Semarang, 2020)
Identifying learning of the information in explanatory text requires creativity in its implementation. One of the things that affect identifying learning of the information in explanatory text is the students’ reading intensity. Therefore, it takes the most effective learning method to be applied and the learning method chosen is the SQ3R method. The purpose of this study was to explain the effectiveness of identifying learning of information in explanatory text by using the SQ3R method based on the reading intensity of the XI grade students at Madrasah Aliyah. The method used in this study was an experimental research design with a quasi-experimental factorial. The sample of this research is students of class IX MAN 2 Kudus. The collection of data uses identifying learning of the explanatory text information and reading intensity test to determine high or low reading intensity. Non-test data collection uses observation and photo documentation. The results of this study were (1) The SQ3R learning method was effective in identifying information in explanatory text for class XI students of Madrasah Aliyah with an increase of 12.23, from an average of 66.51 to 78.74. This is evidenced by the sign value=0.000<0.05, which means that there is a significant difference in the learning outcomes of the experimental group pre-test post-test which is used the SQ3R learning method. Meanwhile, the ability to identify information in explanatory text to students with low reading intensity treated with the SQ3R method, and an average value is 67. Identifying Learning of the information in explanatory text based on reading intensity of the XI grade students at Madrasah Aliyah by using the SQ3R is an effective learning method. The result of this learning has increased by 12.23, from an average of 66.51 to 78.74. This is evidenced by the sign value=0.000<0.05, which means that there is a significant difference in the learning outcomes of the experimental group pretest posttest using the SQ3R learning method